Effects of a multifaceted intervention QI program to improve ICU performance - Anders Ersson; Anders Beckman; Johan Jarl; Jonas Borell (BMC, 2018)
Abstract Background To benefit from the increasing clinical evidence, organisational changes have been among the main drivers behind the reduction of ICU mortality during the last decade. Increasing demand, costs and complexity, amplifies the need for optimisation of clinical processes and resource utilisation. Thus, multidisciplinary teamwork and critical care processes needs to be adapted to profit from increased availability of human skill and technical resources in a cost-effective manner. Inadequate clinical performance and outcome data compelled us to design a quality improvement project to address current work processes and competence utilisation. Methods During revision period, clinical processes, professional performance and clinical competence were targeted using "scientific production management methodology" approach. As part of the project, an intensivist training program was instituted, and full time intensivist coverage was obtained in the process of creating multi-professional teams, composed of certified intensivists, critical care nurses, assistant nurses, physiotherapists and social counsellors. The use of staff resources and clinical work-processes were optimised in accordance with the outcome of a "value stream mapping". In this process, efforts to enhance the personal dynamics and performance within the teams were paramount. Clinical and economic outcome data were analysed during a seven year follow up period. Results • Consecutive reduced overall ICU (24%) and long-term (600 days) mortality. The effect on ICU mortality was especially pronounced in the subgroup of patients > 65 years (30%) • Consecutive reduced length of stay (43%, septic patients) and time on ventilator (for septic patients and patients > 65 years of age (23 resp.52%). • Substantial increase in life years gained (13,140 life years) as well as quality-adjusted life-years (9593 QALY: s) over the study period. • High cost-effectiveness as ICU costs were  reduced while patient outcomes were improved. Disregarding the cost reduction in ICU, the intervention is highly cost effective with cost- effectiveness ratios of (75€/QALY) and (55€ / life year) Conclusions We have shown favourable results of a QI project aiming to improve the clinical performance and quality through the development of multi-professional interaction, teamwork and systematic revisions of work processes. The economic evaluation shows that the intervention is highly cost-effective and potentially dominating.